Potentiating Loopholes: How Erratic and Piecemeal Implementation of the 1970 UNESCO Convention Has Failed to Protect Cultural Antiquities - Kuzma, William (The Columbia Journal of Law & the Arts, 2019)
Despite centuries-old international concerns, American protection of international cultural antiquities is a relatively recent phenomenon. For example, the United States joined a 1954 multilateral treaty on the protection of cultural antiquities only once the treaty had become binding international customary law, and thus likely binding on the United States nonetheless. The United States has been reticent to join many of the major treaties that protect cultural antiquities, and its adoption of these treaties remains piecemeal and inconsistently enforced. There are loopholes in the present international system that continue to permit looting and pillaging to take place worldwide. In this Note, I posit that the current implementation scheme of the 1970 UNESCO Convention on the Means of Prohibiting the Illicit Import, Export and Transfer of Ownership and Cultural Property (1970 UNESCO Convention), both in the United States and in other countries, creates these loopholes, which in turn render the entire system ineffectual. Despite the many attempts at creating broad, multilateral conventions to globally protect cultural antiquities, the United States is only party to two sections of the 1970 UNESCO Convention,9 and it only joined the 1954 Hague Convention in 2009. Additionally, joining the 1954 Hague Convention was merely a formality for the United States because several provisions had already become customary international law and were thus binding on the United States nonetheless.10 As I will show below, the United States’ failure to fully adopt international law on the protection of cultural antiquities hinders the judiciary, as well as our fellow signatories to the 1970 UNESCO Convention, in protecting international cultural antiquities.